Confession as a Ground for Case Termination in KPPU from the Perspective of Ibn Qayyim al-Jauziyah (A Study of Decision Number 04/KPPU-I/2024) - Madinah Asri Putri Andarin; Mustapa Khamal Rokan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study analyzes the position of confession as a ground for case termination in KPPU Decision Number 04/KPPU-I/2024 and examines it from the perspective of Ibn Qayyim al-Jauziyah. The background of this research is based on the behavioral change mechanism introduced under KPPU Regulation Number 2 of 2023, which allows the reported party to acknowledge the alleged violation and submit commitments for behavioral improvement, as well as concerns that confession may become a shortcut that weakens the deterrence function and the protection of public interests. This study employs normative juridical research using the statutory approach and the conceptual approach. Legal materials were collected through library research and analyzed qualitatively using deductive reasoning. The findings indicate that confession is not the sole basis for case termination but rather an initial requirement to enter the behavioral change mechanism. The termination of the case in KPPU Decision Number 04/KPPU-I/2024 was carried out after the commitments to behavioral change had been declared fulfilled through a process of supervision and verification in accordance with KPPU Regulation Number 2 of 2023. From the perspective of Ibn Qayyim al-Jauziyah, confession (iqrār) is a highly authoritative form of evidence but cannot stand alone without supporting proof capable of revealing the objective truth. Therefore, the case termination mechanism is fundamentally consistent with the legal thought of Ibn Qayyim al-Jauziyah. However, the effectiveness and legitimacy of case termination ultimately depend on the objectivity and accountability of the verification process regarding the implementation of the behavioral change commitments.